Cognitive Dysfunction and Age-Related Macular Degeneration. (May 2014) - Rozzini, Luca; Riva, Maddalena; Ghilardi, Nausica; Facchinetti, Paola; Forbice, Eliana; Semeraro, Francesco; Padovani, Alessandro
Several previous studies showed that age-related macular degeneration (AMD) and Alzheimer's disease (AD) share common risk factors and histopathology changes, and there is epidemiological evidence linking AMD to cognitive impairment. We tested this theory in 51 patients with late-stage AMD and 24 controls by analyzing their neuropsychological profiles. In this study, data showed that patients affected by late-stage AMD have a worse global cognitive function than those of the controls and, in particular, show worse performances in memory tasks. Moreover, patients affected by the dry form of AMD are significantly impaired in executive functions in addition to memory. Data support the hypothesis of a possible association between AMD and cognitive impairment. In particular, patients affected by the dry form of AMD may be at greater risk of developing subsequent dementia.